Efektivitas Metode Penyelesaian Sengketa Alternatif dalam Kasus-Kasus Hukum Keluarga - Silitonga, Saritua (Dinasti Review Publisher, 2024)
This research aims to provide a description of the case in question, namely the lack of recognition of conflict management in the family environment with respect to the division of property and inheritance. Such recognition could prevent quarrels that result from a lack of understanding of each other’s needs and expectations. This research will describe how the law in Indonesia can be a bridge in the process of inheritance disputes in the family environment by providing a description of the case of division of inheritance. The research method used is descriptive qualitative with a case study method. The findings of the research demonstrated that certain individuals had not fully implemented an effective conflict management strategy